Rotational Entropy of an Annular Iterated Functions System. Issue 2 (3rd July 2021) - Rezaei, Fatemeh; Nia, Mehdi Fatehi
Abstract: In this article, we consider an iterated functions system (IFS) whose functions are homeomorphisms on an annulus. We define rotational spanning and separating sets for the IFS and then provide two definitions for the rotational entropy of the IFS. We show that in the IFSs, the rotational entropy is a topological invariant. We prove that the rotational entropy of an annular IFS is equal to the rotational entropy on its non-wandering set for sequences of functions with a specific condition.